The interconnectedness of financial inclusion and bank profitability in rising economic powers : evidence from heterogeneous panel analysis - Yanqi, Wang; Muhammad, Ali; Asadullah, Khaskheli; Komal, Akram Khan; Puah, Chin Hong (Emerald Publishing Limited, 2023)
Purpose – The objective is to assess the relationship between financial inclusion and bank profitability in emerging economies, i.e. “Bangladesh, Egypt, Indonesia, Mexico, Nigeria, Pakistan, Philippines, and Vietnam”. Design/methodology/approach – The second-generation econometrics of panel data has been applied to examine the cross-section independence and control the heterogeneity between cross sections. Additionally, the authors employ the following tests for the analysis: “the unit root test, Westerlund’s (2007) bootstrap cointegration, Pedroni cointegration, fully modified ordinary least square (FMOLS), and heterogeneous panel causality techniques”. The annual data consist of the period from 2000 to 2019. Findings – The findings reveal that financial inclusion fosters bank profitability. Therefore, easier access to financial services and products will maximize banks’ profitability. Additionally, the association between financial inclusion and bank profitability is unidirectional. Originality/value – This research is a first attempt to bring a novel contribution to the subject of emerging economies by investigating the association between financial inclusion and bank profitability. Another unique addition to the literature is the use of a novel financial inclusion index. At last, a panel cointegration technique, FMOLS and heterogeneous panel non-causality tests are taken into consideration for the in-depth analysis